Days of destruction, days of revolt - Hedges, Chris (Nation Books, 2012)
"In the vein of Let Us Now Praise Famous Men, Pulitzer Prize winner and bestselling author Chris Hedges and American Book Award winning cartoonist Joe Sacco bring us a searing on-the-ground report on the crisis gripping underclass America and crime-ridden poverty enclaves--in prisons, urban slums, and rural communities--metastasizing around the nation"--